Ontology development for ETL process design - Ta'a, Azman; Abdullah, Mohd Syazwan (IGI Global, 2013)
The Extract, Transform, Load (ETL) process design is difficult to perform because of the ambiguity of user requirements and the complexity of data integration and transformation.Current studies have explored the ontology-based approach to overcome these limitations by reconciling the semantics of user requirements within the ETL process design for easy generation of the ETL process specification. The ontology for ETL process activities has been developed by using the Requirement Analysis Method for ETL Processes (RAMEPs) that is gathered from the perspectives of organization, decision-maker, and developer. Therefore, the ontology is used to generate the ETL process specification for a student affairs’ Data Warehouse (DW) system.The correctness of the ontology model was validated by using an appropriate reasoner.Moreover, the process of ontology development for the case study is presented and shows how the ontology-based approach was successful in implementing the design and generating the ETL process specification.